Politik Hukum Penempatan Ibu Kota Negara Indonesia Di Kalimantan Timur Dikaitkan Dengan Pembangunan Ekonomi Nasional - Dina Febri Yulita; Dodi Haryono; Ledy Diana (Jurnal Ilmiah Wahana Pendidikan, 2023)
The relocation of the capital city dominates the country due to the country's regional development goals, mitigation of the risk of rebellion, decisions of the country's leaders, the problem of flooding in the capital, the country's former low, and infrastructure development. The discourse on moving the capital city has appeared several times during the presidential administration. Then during the administration of President Joko Widodo, discourse reappeared to move the national capital. President Joko Widodo decided to make parts of North Penajem Paser and Kutai Kartanegara in East Kalimantan the location for Indonesia's new capital. Law Number 3 of 2022 concerning the State Capital is a legal political form of moving the national capital. The urgency of relocating the capital as expressed by President Joko Widodo at the Annual Session of the People's Consultative Assembly, is based on the fact that economic activity is concentrated in Jakarta and Java, which has created an economic gap between Java and outside Java. This inequality causes a concentration of economic investment. The concentration of economic investment in Jakarta has resulted in a very low poverty rate in Jakarta compared to other regions. Therefore, it is necessary to examine how the legal politics of placing the Indonesian state capital in East Kalimantan are related to national economic development. The type of research used by the author is normative legal research. Normative legal research is carried out by examining library materials or secondary data. The data collection technique in this research is library research. This technique can be used to limit the use of document studies or library materials, namely secondary data. In writing this thesis, the author uses qualitative data analysis which produces descriptive data. With qualitative analysis, a researcher aims to understand or understand the symptoms he is studying. The results of this thesis research state that the placement of the Indonesian state capital from Jakarta to East Kalimantan is based on the philosophical, sociological, and juridical foundations of Law Number 3 of 2022 concerning the State Capital. Then the legal politics of placing the national capital in East Kalimantan is linked to national economic development so that in the future, the burden on the island of Java, especially Jakarta, can be reduced. In addition, the placement of the capital city in East Kalimantan is to balance the Indonesian economy, including to the eastern part. The government believes that this will bring a number of benefits in the economic field. However, moving the nation's capital should have been done when the country was ready. Legal Politics, National Capital, National Economic Development, East Kalimantan